2016
DOI: 10.1039/c5gc02153g
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid tethered post functionalized ZIF-90 framework for the cycloaddition of propylene oxide and CO2

Abstract: Covalent post functionalized ZIF-90 with pyridinium based ionic liquid was prepared and used as catalyst for the solventless synthesis of propylene carbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(81 citation statements)
references
References 98 publications
4
73
0
4
Order By: Relevance
“…Imidazoliumbased IL-decorated catalysts such as UiO-67-IL [41] and IL@MIL- [42] were reported as active catalysts for CO 2 /ECH coupling reactions (Table 3, entries 1a nd 2). At high reaction temperature (120 8C), IL-ZIF-90 [44] afforded 83 %c onversion of ECH within 3h (Table 3, entry 4). Ding et al [43] reported that imidazolium-based poly(ionic liquid)s confined in MOFs, polyILs@MIL-101, afforded an ECH carbonatey ield of 94 %a t7 08Cf or 24 h with the use of 100 mg of catalyst (Table 3, entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Imidazoliumbased IL-decorated catalysts such as UiO-67-IL [41] and IL@MIL- [42] were reported as active catalysts for CO 2 /ECH coupling reactions (Table 3, entries 1a nd 2). At high reaction temperature (120 8C), IL-ZIF-90 [44] afforded 83 %c onversion of ECH within 3h (Table 3, entry 4). Ding et al [43] reported that imidazolium-based poly(ionic liquid)s confined in MOFs, polyILs@MIL-101, afforded an ECH carbonatey ield of 94 %a t7 08Cf or 24 h with the use of 100 mg of catalyst (Table 3, entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…[26,27] Over the past decades, many supported IL-phase( SILP) heterogeneousc atalysts with silicag els, SiO 2 / Al 2 O 3 ,a ctivated carbon,T iO 2 ,a nd mesoporous silica as porous support materials have been reported for various catalytic reactions. [42][43][44][45][46] However, the synthesis of IL-immobilized metalorganic heterogeneous catalysts that efficientlyc atalyze cycloaddition reactions without ac ocatalystu nder mild conditions of temperature and CO 2 pressure remains challenging. Therefore, several approaches have been established for the synthesis of efficient IL-based poroush eterogeneousc atalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Tharun and co-workers [140], a novel heterogeneous one-component catalyst was developed by covalent post functionalization of zeolitic imidazolate framework-90 (ZIF-90) with a pyridinium based IL to generate IL supported ZIF-90 (IL-ZIF-90). The synthesized catalyst has been successfully employed for the solventless cycloaddition of epoxides and CO 2 to yield cyclic carbonates under mild reaction conditions.…”
Section: Post Synthesis Methodsmentioning
confidence: 99%
“…In view on the importance of the chemical fixation of CO 2 , a broad range of homogeneous and heterogeneous catalysts including organic bases, ionic liquids, supported catalysts, organic copolymers, and carbon materials have been investigated for the cycloaddition of CO 2 with epoxides . Among these materials, different polymer‐supported catalysts with desirable selectivity have been developed which are superior to homogeneous catalysts in terms of catalyst stability and separation of catalyst . However, some of the catalysts and protocols have drawbacks such as the use of a high temperature and CO 2 pressure, metallic ions, high‐cost procedures for product separation and/or catalyst synthesis, low activity, poor stability, unsatisfactory reusability, and need a long reaction time.…”
Section: Introductionmentioning
confidence: 99%